The Effectiveness of the Problem-Solving Method in Improving the ability of Writing Narrative Paragraph of Students of Class XI MAN 4 Bone - Jumriati Jumriati; Herawati Arief S; Rosary Iriany (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to apply the Problem-Solving method to improve students' ability to write narrative paragraphs. This research is classroom action research carried out in 2 cycles. The subjects in this study were class studentsXI MAN 4 Boneswhich totaled 30 students. The analysis technique in this study used quantitative and qualitative analysis. Data collection techniques in this study were tests, observations, and interviews. While the object of this study is the application of the Problem-Solving method in improving the ability to write narrative paragraphs. In the pre-action students' writing results obtained an average value of 71.13. Cycle I as many as 17 students with a percentage level of 56.7% reached the complete category while those who did not complete 13 students with a percentage level of 43% obtained an average value of 72.7 thus this study continued to the second cycle because the frequency of completeness had not reached 70% of the indicator setting. In cycle II as many as 26 students were categorized as complete with a percentage level of 87% while the number of students who had not reached completeness was 4 students with a percentage level of 13% so the results of the implementation of cycle II obtained an average value of 79.93. Thus, it can be concluded that the application of the Problem-Solving method in improving the ability to write narrative paragraphs of class studentsXI MAN 4 Bonescategorized as very good.